Powerful sources of pulse high-frequency electromechanical transducers for measurement, testing and diagnostics - Plesnetsov, S.Yu.; Petrishchev, O.N.; Mygushchenko, R.P.; Suchkov, G.M.; Sotnik, S.V.; Kropachek, O.Yu. (Електротехніка і електромеханіка, 2018)
Aim. Development of powerful current radio pulses generators (CRPG) for powering high-frequency electromechanical
transducers based on IGBT transistors. Methodology. To carry out the research, the statements of the magnetic and
electromagnetic fields interaction with electric and ferromagnetic material, electric circuits, structure of radio electronic devices
theory were used. Results. The main provisions for creating powerful broadband generators for powering electromechanical
transducers based on IGBT transistors are determined. It is shown that the generators intended for use in measurements, testing
and diagnostics should provide adjustment of the frequency and duration of the output current pulses, and also provide current in
the transducer inductor of several hundred amperes. The connection between the power frequency of the resonant
electromechanical transducer and the gap between the transducer and the surface of the metal being diagnosed is established. A
CRPG variant for powering electromechanical transducers in the frequency range 1 ... 3 MHz and the duration of current pulses
of 1 ... 20 periods of the filling frequency is developed and manufactured. The peak current in the inductor of a high-frequency
electromechanical transducer has reached 450 A. Novelty. For the first time, the possibility of using powerful IGBT transistors in
electronic devices working in a key mode in push-pull circuits for feeding high-frequency electromechanical transducers is
shown. Practical value. Using the results obtained will allow the creation of new instruments for measurement, control and
diagnostics with wider characteristics. Цель работы. Разработка основных положений по созданию мощных источников импульсов тока для питания
высокочастотных электромеханических преобразователей для измерений, контроля и диагностики
электротехнических устройств на базе силовых IGBT транзисторов. Методика. Для проведения исследований
использовались положения теории взаимодействия магнитных и электромагнитных полей с электропроводным и
ферромагнитным материалом, электрических цепей, построения электронных устройств. Результаты. Определены
основные положения по созданию мощных широкополосных генераторов для питания электромеханических
преобразователей на базе силовых IGBT транзисторов. Показано, что генераторы, предназначенные для
использования в измерениях, контроле и диагностике, должны обеспечивать регулировку частоты и длительности
импульсов выходного тока, а также обеспечивать ток в катушке преобразователя величиной до 450 A. Установлена
связь между частотой питания резонансного электромеханического преобразователя и зазором между
преобразователем и поверхностью диагностируемого металла. Разработан и изготовлен вариант ИИТ для питания
электромеханических преобразователей в диапазоне частот 1…3 MHz и длительности импульсов тока 1…20
периодов частоты заполнения. Пиковая величина тока в катушке высокочастотного электромеханического
преобразователя достигла 450 A. Научная новизна. Впервые показана возможность применения силовых IGBT
транзисторов в электронных устройствах, при ключевом режиме работы в двухтактных схемах для питания
высокочастотных электромеханических преобразователей. Практическая значимость. Использование полученных
результатов позволит создавать новые приборы для измерений, контроля и диагностики с улучшенными
характеристиками.